Climate Crisis and Social Inequality: A Bibliometric Review of Environmental Sociology Research (2014–2024) - Resita Aprilia S; Heriyanti, Lesti; Wijayanti, Ayu; Pakpahan, Fransiskus Novrianto (Lenggogeni Data Publishing, 2024)
Abstract The climate crisis and social inequality represent two of the most pressing challenges of the 21st century, deeply interconnected and necessitating rigorous sociological inquiry to examine how marginalized communities disproportionately bear the brunt of environmental harm. While qualitative and case-study approaches have dominated the field, a significant gap remains in systematic bibliometric analyses to quantify research trends, influential works, and emerging discourses. This study aims to map the evolution, key themes, and gaps in environmental sociology literature from 2014 to 2024, particularly focusing on the relationship between climate change and social inequity. Employing a bibliometric methodology, we analyzed 173 Scopus-indexed documents using VOSviewer, incorporating co-citation analysis, bibliographic coupling, and keyword co-occurrence mapping. Findings reveal dominant themes such as environmental justice, socio-ecological resilience, and differential vulnerabilities, with seminal influences from Barnett (2005) on hydrology and Adger (2000) on coastal resilience. However, research on intersectional vulnerabilities—particularly gender and Indigenous adaptation strategies—remains underrepresented, alongside a geographical bias favoring Global North studies. The implications underscore the need for interdisciplinary approaches integrating traditional ecological knowledge with scientific modeling, as well as inclusive policy frameworks for just transitions. Future research priorities include examining AI’s impact on labor market disparities, human-AI collaboration in strategic sectors, and ethical governance for sustainable work. This study provides a foundational synthesis for scholars and policymakers to design evidence-based, equity-centered climate interventions, ensuring that mitigation and adaptation strategies prioritize the most vulnerable while leveraging innovation for systemic resilience.